The effectiveness of the combined PBL and Tencent Conference online teaching mode in the clinical internship teaching of cardiac surgery. - Xiuwen Chen; Yao Xiao; Yunhui You; Jianxi Zhu; Shiqing Liu; Huiqiong Chen; Hong Zhu (PLoS ONE)
Background Educators increasingly emphasise the importance of clinical medical education reform, particularly the innovation of teaching models. Clinical internships in cardiac surgery are an essential stage in the development of medical students. Currently, it is still dominated by the traditional lecture mode. Therefore, exploring a new teaching model is a critical way to improve the quality of clinical internship teaching. Objectives To investigate the effectiveness of the combined PBL and Tencent Conference online teaching mode in the clinical internship teaching of cardiac surgery. Methods This historical controlled trial was conducted from September 2022 to January 2023. A total of 34 participants from the graduating class of 2020 took the combined PBL and Tencent Conference online teaching mode. 42 participants from the graduating class of 2021 adopted the traditional teaching method and were enrolled as a control group. All participants completed a questionnaire designed by the researcher to assess teaching quality. The questionnaire was filled out sequentially according to the chronological order of pre-internship, during the internship, and post-internship. Results There was a statistically significant difference between the group of Tencent Conference online teaching based on the PBL mode and the group of traditional teaching mode in terms of the degree of participation (experience, hands-on opportunities, etc.), the degree of teacher-student interaction (questions, communication, etc.), and the degree of acceptance and understanding (key points, difficulties, and other learning concerns) in the class learning process during the internship (p < 0.05). The results of the survey also showed that there was a significant difference between the two groups in the scores of the degree of mastery and use of history taking in cardiac surgery and the degree of mastery and use of ancillary tests (application and interpretation of each test) after the internship (p < 0.05). Conclusions The traditional approach currently used by most educators does not enable cardiac surgery students to transform theory fully. The PBL teaching method can stimulate students' interest in learning and cultivate their comprehensive ability to a certain extent. Future educators should flexibly adapt the teaching method to the learning situation, develop a reasonable teaching mode of clinical internship, and ensure quality.